Interdisciplinary game in english language with digital RPG (Revista Contexto & Educação, 2026)
The general objective of this study was to propose an interdisciplinary game with digital RPG (Role-Playing Game) in English. This is an exploratory descriptive research, which describes how the game was built and its components aligned with the BNCC. One of the authors of this study teaches English and Portuguese at the School called Escola da Floresta Olho da Coruja (EFOC), located in Chapada - RS, which works with the project methodology in an interdisciplinary way. Thus, we chose a plot that not only met the theme of the annual project, but was also capable of encompassing knowledge inherent to all curricular components of elementary school. Following the theme listed for 2024, “Living with insects”, the digital RPG game for classroom use , named “Insect Forest”, was created. The RPG Maker MZ software was purchased through the Steam platform, where it is possible to purchase games and computer software. Avatars representing the school's teachers and students were created, and a map of the school was developed, representing its environments. All dialogues are in English, except in one phase, which requires knowledge of the Portuguese language. In each phase, the student/player will face puzzles and, upon solving them, will advance to the next phase and receive “special powers”. It is believed that the game's proposed challenges contribute to the protagonism of the students, who must make decisions at each phase and enable the review of the curricular content included in the game.
Keywords: Elementary Education; Pedagogical practice; English language; Digital RPG